Transaction costs in an illiquid order‐driven market. (16th April 2015) - Marshall, Ben R.; Nguyen, Nhut H.; Visaltanachoti, Nuttawat
Abstract: Transaction costs in many international equity markets are much larger than those in the USA. This raises questions such as what trade size these reported trading costs relate to and whether investors can reduce trading costs by timing their trades. We show, using data from the order‐driven New Zealand market, that transaction costs are frequently lower for larger trades, particularly in small stocks, and investors are able to reduce costs by timing their transactions. While investors who require immediate execution incur transaction costs that are much higher than reported average costs, patient investors can trade at much better rates.